Social provisions in patients with mitochondrial diseases - Deborah Schofield; Rupendra Shrestha; Carolyn M Sue; Ryan Davis; Sameen Haque; Karen Crawley (BMJ Neurology Open, 2024)
Background Mitochondrial diseases often follow a chronic, multimorbid disease course in adults. Like other chronic conditions, mitochondrial diseases present a challenge to public and community health models and patients are potentially at higher risk of social isolation and loneliness. However, there is lack of data on social provisions in mitochondrial diseases.Methods We performed a cross-sectional observational study on patients with a confirmed genetic or clinical diagnosis of mitochondrial disease, recruited between September 2018 and December 2021. Participants completed the Social Provisions Scale (SPS) as a measure of social support. Designated carers similarly completed the SPS in carer-specific questionnaires.Results 95 mitochondrial disease patients and 24 designated carers completed the SPS. Social provisions were met for all six subscales of SPS in the mitochondrial disease cohort: (1) guidance 90.5% (n=86), (2) reassurance of self-worth 82.8% (n=77), (3) social integration 88.4% (n=84), (4) attachment 83.2% (n=79), (5) opportunity of nurturance, 61.1% (n=58) and (6) reliable alliance 95.8% (n=91). All social provisions were also met in the carer cohort.Conclusion Patients with mitochondrial diseases and their carers demonstrate a high perceived level of social support in the setting of a tertiary referral centre specialised in mitochondrial disease despite the burden of chronic disease.